Comparison of Fine Needle Aspiration Cytology Versus Open Biopsy for Chronic Cervical Lymphadenopathy (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Open biopsy is considered ideal for diagnosis of cervical lymphadenopathy. Fine needle aspiration cytology (FNAC) is safe, less invasive and cost effective as compared to open biopsy. However, its diagnostic efficacy remains in debates. This study was conducted to know how accurately FNAC can detect the pathology as compared to open biopsy. Objective: To compare the diagnostic efficacy of FNAC and open biopsy for chronic cervical lymphadenopathy. Methodology: This comparative study was conducted at department of Surgery, Lahore General Hospital, Lahore. The study was completed in six months including 96 patients with diagnosis of cervical lymphadenopathy. All the patients had FNAC followed by open biopsy. The diagnostic efficacy of the two techniques was compared by calculating sensitivity, specificity and diagnostic accuracy of each technique. Results: The diagnostic accuracy of FNAC for tuberculosis, metastatic carcinoma, Hodgkin’s lymphoma, non Hodgkin’s lymphoma, reactive hyperplasia and chronic nonspecific lymphadenopathy were 92.6%, 100%, 85.7%, 87.5%, 100% and 100%, respectively. Conclusions: FNAC is reliable and safe technique with high diagnostic efficacy and should be preceded as first line investigation in management of cervical lymphadenopathy.
Keywords: Cervical lymphadenopathy; fine needle aspiration cytology; open biopsy